Endothelial Caveolin-1 regulates the radiation response of epithelial prostate tumors - Klein, Diana; Herskind, Carsten; Maier, Patrick (Oncogenesis, 2015)
The membrane protein caveolin-1 (Cav1) recently emerged as a novel oncogene involved in prostate cancer progression with opposed regulation in epithelial tumor cells and the tumor stroma. Here we examined the role of stromal Cav1 for growth and radiation response of MPR31-4 prostate cancer xenograft tumors using Cav1-deficient C57Bl/6 mice. Syngeneic MPR31-4 tumors grew faster when implanted into Cav1-deficient mice. Increased tumor growth on Cav1-deficient mice was linked to decreased integration of smooth muscle cells into the wall of newly formed blood vessels and thus with a less stabilized vessel phenotype compared with tumors from Cav1 wild-type animals. However, tumor growth delay of MPR31-4 tumors grown on Cav1 knockout mice to a single high-dose irradiation with 20 Gray was more pronounced compared with tumors grown on wild-type mice. Increased radiation-induced tumor growth delay in Cav1-deficient mice was associated with an increased endothelial cell apoptosis. In vitro studies using cultured endothelial cells (ECs) confirmed that the loss of Cav1 expression increases sensitivity of ECs to radiation-induced apoptosis and reduces their clonogenic survival after irradiation. Immunohistochemical analysis of human tissue specimen further revealed that although Cav1 expression is mostly reduced in the tumor stroma of advanced and metastatic prostate cancer, the vascular compartment still expresses high levels of Cav1. In conclusion, the radiation response of MPR31-4 prostate tumors is critically regulated by Cav1 expression in the tumor vasculature. Thus, Cav1 might be a promising therapeutic target for combinatorial therapies to counteract radiation resistance of prostate cancer at the level of the tumor vasculature.